Forging New Frontiers: Indonesia's Automotive Interests in the Indonesia-Mozambique Preferential Trade Agreement - Athallah, Ilham Dary; Khairia, Hayara; Husna, Tsabita (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2025)
This study investigates Indonesia's strategic interest in prioritizing the automotive sector within the Indonesia-Mozambique Preferential Trade Agreement (IM-PTA), its inaugural African bilateral pact. Contrasting with the agreement's dominant agricultural focus reflected in the tariff schedules for both nations, as both countries have plenty of competitive advantages in the agricultural sectors, this paper explores the unique phenomenon of Indonesia lobbying for the automotive sector as part of the manufacturing industry. Employing Neoclassical Realism (NCR) through a qualitative case study, we analyze how systemic pressures—including global trade uncertainties and Africa's market potential—interacted with domestic variables like elite vision (President Jokowi's economic diplomacy), state capacity, and automotive industry influence. Findings suggest the automotive focus emerged from a convergence of leadership goals and industry requirements. Mozambique was selected due to potential as a strategic gateway. Conclusively, NCR provides a robust framework explaining this foreign economic policy decision as an outcome of interacting systemic and domestic influences.